Bioengineering pediatric scaffold‐free auricular cartilaginous constructs. (21st November 2016) - Akbari, Pedram; Waldman, Stephen D.; Cushing, Sharon L.; Papsin, Blake C.; Propst, Evan J.; Weber, Joanna F.; Yeger, Herman; Farhat, Walid A.
Abstract : Objective: The use of exogenous materials as scaffolds in cartilage tissue engineering has limited the clinical application of resultant constructs due to the risk of postoperative complications. In an effort to minimize such complications, we aim to generate human, scaffold‐free auricular cartilaginous constructs. Study Design: Laboratory study using pediatric auricular cartilage. Methods: Remnant, normal pediatric auricular cartilage samples that would have otherwise been discarded were collected and digested to free cells. Harvested cells were cultured and expanded in vitro for two passages and plated as micromass cultures. The culture medium was replaced with a chemically defined chondrogenic medium, and cellular monolayers surrounding micromass cultures were continuously scraped off. Constructs were allowed to mature for a period of 8 weeks. Results: Micromass constructs showed mechanical stability and structurally resembled native auricular tissue, with a perichondrium‐like layer of cells surrounding the inner cartilaginous zone. Constructs accumulated equivalent sulphated glycosaminoglycan and 50% of collagen content compared to native auricular cartilage by mass, while displaying 156% more cellularity. Conclusions: High‐density micromass cultures of pediatric auricular chondrocytes can generate stable cartilaginous constructs following prolonged chondrogenic inductions in vitro. This technique is an essential step toward the development of three‐dimensional constructs to recreate clinically applicable auricular cartilaginous constructs. Level of Evidence: NA. Laryngoscope, 127:E153–E158, 2017